A rare cause of mechanical intestinal obstruction in geriatric population: Gallstone ileus three cases - Bozdağ, Ahmet; Kutluer, Nizamettin; Gültürk, Barış; Aksu, Ali; Bozan, Mehmet Bugra; Gönen, Ayşe Nur; Böyük, Abdullah (My University, 2019)
Gallstone ileus is an uncommon cause of mechanical intestinal obstruction. It often occurs in the elderly and patients with recurrent cholecystitis episodes. Making diagnosis can be challenging since the entity lacks any specific symptoms or signs. A vast number of patients were reported to be diagnosed during the course of operation. Gallstone ileus has high morbidity and mortality since it occurs in the geriatric population who already has various comorbidities. Abdominal CT provides quite beneficial information for the diagnosis of these patients. Appropriate treatment option should be selected for each patient considering some personal factors (such as age, comorbidity, clinical stability). The article presents three cases with gallstone ileus causing mechanical intestinal obstruction.
Keywords: Genel ve Dahili Tıp; Patoloji; Geriatri ve Gerontoloji; Gastroenteroloji ve Hepatoloji